Abundance of Associated Arbuscular Mycorrhizal Fungi with Pioneer Plants in Affected Area by Mount Merapi Eruption - Oktira Roka Aji; Inggita Utami; Cucu Cahyanti (Institut Pertanian Bogor (IPB University), 2021)
Arbuscular mycorrhizal fungi (AMF) with mutualism symbiosis with plants are associated with the Fabaceae family's pioneer plants. This study aims to determine the percentage of AMF in the roots and the AMF spore's abundance in the rhizosphere of pioneer plants Calopogonium mucunoides Desv. and Vigna Unguiculata (L.) Walp in Mount Merapi National Park after the 2010 eruption. The methods used for root infection analysis were slide methods and root staining, while spore analysis was wet sieving methods. The results showed the highest percentage of AMF infection in C. mucunoides root was found in an area with moderate damage. The highest percentage of AMF infection in V. unguiculata was found in an area with minor damage. The highest number of spores in the two plants' rhizosphere soil was found in an area with minor damage with an average of 10.4 and 9. The levels of damage by Mount Merapi's eruption did not significantly affect the percentage of AMF infection and the number of spores. Glomus dominates all study sites in both plants. Soil organic carbon is one of the abiotic factors correlated with the number of spores in rhizosphere soil.